Strong hydraulic segmentation and leaf senescence due to dehydration may trigger die-back in Nothofagus dombeyi under severe droughts: a comparison with the co-occurring Austrocedrus chilensis - Scholz, Fabian Gustavo (2014)
Die-back was observed in South America temperate forests during one of the most severe droughts of the 20th century (1998–1999). During this drought Austrocedrus chilensis trees survived, whereas trees of the co-occurring species (Nothofagus dombeyi) experienced symptoms of water stress, such as leaf wilting and abscission, before tree die-back occurred. We compared hydraulic traits of these two species (a conifer and an angiosperm species, respectively) in a forest stand located close to the region with records of N. dombeyi mass mortality. We asked whether different hydraulic traits exhibited by the two species could help explain their contrasting survivorship rates. Austrocedrus chilensis had wide leaf safety margins, which appear to be the consequence of relatively high leaf-and-stem capacitance, large stored water use, strong stomatal control and ability to recover from embolism-induced loss of leaf hydraulic capacity. On the other hand, N. dombeyi even though had a stem hydraulic threshold of −6.7 MPa before reaching substantial hydraulic failure (P88), leaf P88 occurred at leaf water potentials of only −2 MPa, which probably are reached during anomalous droughts. Massive mortality in N. dombeyi appears to be the result of the total loss of leaf hydraulic conductance leading to leaf dehydration and leaf drop. Drought occurs during the summer and it is highly likely that N. dombeyi cannot recover its photosynthetic surface to produce carbohydrates required to avoid tissue injury in the winter season with subfreezing temperatures. Strong hydraulic segmentation in N. dombeyi does not seem to have an adaptive value to survive severe droughts.